Value Addition and Labour Productivity in the Malaysian Furniture Industry Between 1986 and 2004 - Chong, Yen Yoon (2009)
The Malaysian furniture industry is the most important sub-sector within the wood-based industry, yet its growth is a matter of intense debate. On a general basis, it is argued that the Malaysian furniture industry is a low wage economy, producing low quality furniture. Therefore, this study aims: (1) to compare the performance of the furniture industry during the periods of the first and second Industrial Master Plans (IMP) of Malaysia, (2) to identify the trend in labour productivity, expressed as the ratios, during the same period, and (3) to quantitatively study the relationship between labour productivity and value addition in the furniture industry. Secondary published data on the furniture industry were collected mainly from the Department of Statistics Malaysia (DOS), for the period 1986 to 2004. A set of productivity indicators such as value added, labour productivity ratio, and capital productivity ratio were used in the analysis, as suggested by the National Productivity Corporation (NPC) Malaysia. During 1986 – 2004, value addition in the furniture industry grew steadily from RM 85 million to RM2,536 million, and labour productivity recorded a positive growth trend from 1990 (RM12,900) to 2004 ((RM32,400). The results showed that there was a positive trend in annual gross output and cost of input, which increased by about RM524 million annually and RM369 million annually, respectively, but the value addition and labour productivity were still low. The continuous growth of output was largely due to the increased number of factories, workforce and gross inputs. However, from the increasing cost of inputs, especially the labour cost and raw materials cost, the Malaysian furniture industry remains low in value addition. It confirms that the Malaysian furniture industry is still a mass producer of commodity-type furniture. This study provides evidence to support the argument that the industrial growth in the Malaysian furniture industry has been driven primarily by incremental input factors.